Effect of temperature on the complexation of NpO2+ with benzoic acid: Spectrophotometric and calorimetric studies. (January 2015) - Yang, Yanqiu; Zhang, Zhicheng; Liu, Guokui; Luo, Shunzhong; Rao, Linfeng
Graphical abstract: Abstract: The equilibrium constants of the 1:1 NpO2 + /benzoate complex were determined by spectrophotometric titrations at variable temperatures ( T = 283 to 343 K) and the ionic strength of 1.05 mol · kg −1 . The enthalpy of complexation at T = 298 K was determined by microcalorimetric titrations. Similar to other monocarboxylates, benzoate forms a weak complex with NpO2 + and the complexation is strengthened as the temperature is increased. The complexation is endothermic and is entropy-driven. The enhancement of the complexation at elevated temperatures is primarily attributed to the increasingly larger entropy gain when the water molecules are released from the highly-ordered solvation spheres of NpO2 + and benzoate to the bulk solvent where the degree of disorder is higher at higher temperatures. The spectroscopic features of the Np(V)/benzoate system, including the effect of temperature on the absorption bands, are discussed in terms of ligand field splitting and a thermal expansion mechanism.